pregnancy and occupation - Maryam Malek (طب کار)
Introduction: Pregnant employees demand special attention from their employers and themselves. In this study,the focus is on the interaction between pregnancy and occupation. Methods: This study was a review article. Authentic articles, sites and books on occupational medicine, fitness for work and obstetrics were used. This study consisted of different parts including: definition of terms, the importance of issue of pregnancy in employees, pregnancy changes that affect fitness to work, some special considerations, prescription of occupational specialist during pregnancy, breastfeeding, and postnatal issues. Results: The workplace hazards to the pregnant employees were factors that were harmful to the health or safety of the mother and/or fetus. These hazards included: physical, chemical, biologic, psychologic and ergonomic-hazard. Pregnancy made changes in fitness of pregnant employees. After delivery attention to the mothers was required, too. Conclusion: After identifying the risks at each workplace, appropriate methods of control could be used. Control of these routine hazards, and vaccinations, were the duties of the occupational physician for pregnant employees.